El País de las Amazonas: Una delimitación imaginada en la cartografía francesa colonial del siglo XVIII - Unigarro, Daniel Esteban (Review of International American Studies, 2024)
Since the mid-16th century, cartographic representations of the New World included a large river that crossed the southern continent from east to west. Despite names such as Santa María de la Mar Dulce or Río de Orellana, in reference to the Spanish captain who led the expedition that made its hazardous discovery in 1542, a mythical European reference ended up prevailing: the Amazons River. This hydronym also became the toponym that since then refers to the extensive basin defined by the wide main channel with its innumerable tributaries. Nevertheless, during the colonial domination period, none of the European empires used the term “Amazon” to officially name any of their jurisdictions in America. Then the aim is to demonstrate how French cartography produced during the 18th century constantly presented and reproduced an imagined territorial delimitation marked as “the Country of the Amazons”, probably in accordance with the French colonial interest in establishing a presence in the region disputed mainly by the Spanish and Portuguese. Although, in the end, such delimitation was just another product of the colonial geographic imagination and, specially, of the mythical imaginaries associated with the region since its discovery.